Penetration tester's open source toolkit - Long, Johnny (Syngress Pub., 2006)
Penetration testing a network requires a delicate balance of art and science. A penetration tester must be creative enough to think outside of the box to determine the best attack vector into his own network, and also be expert in using the literally hundreds of tools required to execute the plan. This book provides both the art and the science. The authors of the book are expert penetration testers who have developed many of the leading pen testing tools; such as the Metasploit framework. The authors allow the reader inside their heads to unravel the mysteries of thins like identifying targets, enumerating hosts, application fingerprinting, cracking passwords, and attacking exposed vulnerabilities. Along the way, the authors provide an invaluable reference to the hundreds of tools included on the bootable-Linux CD for penetration testing. * Covers both the methodology of penetration testing and all of the tools used by malicious hackers and penetration testers * The book is authored by many of the tool developers themselves * This is the only book that comes packaged with the "Auditor Security Collection"; a bootable Linux CD with over 300 of the most popular open source penetration testing tools.
Title from title screen.
Keywords: počítačová bezpečnost; zabezpečení počítačových sítí; ochrana softwaru; informační bezpečnost; computer security; computer network security; software protection; information security; elektronické knihy; electronic books